Patients erxperiences and attitudes towards electroconvulsive therapy - A descriptive study - Ranasinghe, P (My University, 2004)
Majority ( 92 percent ) 0f patients found ECT a helpful treatment and not particularly frightening . Eighty four percent ( 84) of the patients agreed that if necessary they would readily have the treatment again. The commonest persistent side effect was memory lapse ( mainly autobiographical memory during the time of treatment) , found in 26 of the patients but they did not find it as irritating or incapacitating . Patients' understanding about the treatment was very poor and it is clear that patients wish to be told more about the treatment. The procedure of obtaining informed consent for ECT appears to be grossly inadequate.